2019
DOI: 10.1093/mnras/stz2717
|View full text |Cite
|
Sign up to set email alerts
|

Generalized model-independent characterization of strong gravitational lenses V: reconstructing the lensing distance ratio by supernovae for a general Friedmann universe

Abstract: We determine the cosmic expansion rate from supernovae of type Ia to set up a databased distance measure that does not make assumptions about the constituents of the universe, i.e. about a specific parametrisation of a Friedmann cosmological model. The scale, determined by the Hubble constant H 0 , is the only free cosmological parameter left in the gravitational lensing formalism. We investigate to which accuracy and precision the lensing distance ratio D is determined from the Pantheon sample. Inserting D an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…We review the precision up to which the lensing distance ratio in Equation (6) can be determined from the Pantheon sample of SNe type Ia, [41], in Section 3.5. The details to set up the angular diameter distance measure from the sample are found in [26]. Section 3.6 sets up theoretical limits on the precision to which H 0 can be determined by Equation (16).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We review the precision up to which the lensing distance ratio in Equation (6) can be determined from the Pantheon sample of SNe type Ia, [41], in Section 3.5. The details to set up the angular diameter distance measure from the sample are found in [26]. Section 3.6 sets up theoretical limits on the precision to which H 0 can be determined by Equation (16).…”
Section: Resultsmentioning
confidence: 99%
“…The term for the spatial curvature with Ω K is discarded, as [64] found that the curvature is compatible with zero. Alternatively, any data-based expansion function can be inserted, as, for instance set up for our approach in [26]. Section 2.5 details these data-based distance measures.…”
Section: Foldmentioning
confidence: 99%
See 3 more Smart Citations